Ethnotheatre and Creative Methods for Teacher Leadership - Cranston, Jerome; Kusanovich, Kristin (Creativity, Education and the Arts, 2016)
This book addresses the lived challenges to teacher leadership. It illustrates an arts-based research approach that effectively highlights the broader context of relational dynamics between adults at school, using one-act plays to open up difficult conversations on complex issues. School leadership has, ostensibly, a performative dimension. Teacher leaders enact leadership from a more vulnerable platform than those with administrative positions, while they try to thrive in roles which are not always clear from their pre-service preparation. Early-career teachers are often not aware of the very real hazards that can accompany their initial foray into leadership. This book encourages creative thinking about how to enact the teacher role to better embed and advocate for a supportive and just system. Jerome Cranston is Associate Professor at the University of Manitoba, Canada. Kristin Kusanovich is Senior Lecturer at Santa Clara University, USA.